2011
DOI: 10.1083/jcb.201012074
|View full text |Cite
|
Sign up to set email alerts
|

Sorting of GPI-anchored proteins into ER exit sites by p24 proteins is dependent on remodeled GPI

Abstract: p24 complexes act as cargo receptors for sorting GPI-anchored proteins into COPII vesicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
135
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(145 citation statements)
references
References 57 publications
8
135
0
1
Order By: Relevance
“…Most eukaryotes have 4 -10 p24 proteins that are classified into four subfamilies (p24␣, -␤, -␥, and -␦) (34). Knockdown or overexpression of a single p24 isoform often leads to mislocalization and degradation of other isoforms (27,28,(35)(36)(37)(38). These observations together with the results of physical interaction studies led to the conclusion that p24 proteins form heteromeric complexes, most likely dimers and tetramers.…”
mentioning
confidence: 79%
See 2 more Smart Citations
“…Most eukaryotes have 4 -10 p24 proteins that are classified into four subfamilies (p24␣, -␤, -␥, and -␦) (34). Knockdown or overexpression of a single p24 isoform often leads to mislocalization and degradation of other isoforms (27,28,(35)(36)(37)(38). These observations together with the results of physical interaction studies led to the conclusion that p24 proteins form heteromeric complexes, most likely dimers and tetramers.…”
mentioning
confidence: 79%
“…However, Jenne et al (39) reported that p24 proteins exist mostly in monomers and dimers in HeLa cells. Although the conclusion is still somewhat controversial, available data suggest that p24 proteins in mammals are in dynamic equilibrium among monomers, dimers, and tetramers (27,36,37). Martens and co-workers (71)(72)(73) proposed another model in which p24 proteins in Xenopus melanotrope cells can function as monomers, and each has an individual role in prohormone processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both PGAP1 and PGAP5 mutant CHO cells, ER-to-Golgi transport was significantly delayed because of impaired concentration of GPI-anchored proteins at the ER-exit sites (73) (Fig. 2B).…”
Section: Er-to-golgi Transport Of Gpi-anchored Proteinsmentioning
confidence: 99%
“…In mammalian cells, two GPI-anchor remodeling reactions in the ER (inositol deacylation by PGAP1 and removal of the side chain EtNP by PGAP5) are required for efficient transport of GPI-anchored proteins between the ER and the Golgi apparatus (37,47,73). In both PGAP1 and PGAP5 mutant CHO cells, ER-to-Golgi transport was significantly delayed because of impaired concentration of GPI-anchored proteins at the ER-exit sites (73) (Fig.…”
Section: Er-to-golgi Transport Of Gpi-anchored Proteinsmentioning
confidence: 99%